Endovascular reconstruction of vertebral artery occlusion prior to basilar thrombectomy in a series of six patients presenting with acute symptomatic basilar thrombosis. (4th June 2013) - Ecker, Robert D; Tsujiura, Crystiana A; Baker, Christopher B; Cushing, Deborah
Abstract : Introduction and purpose: Symptomatic acute basilar thrombosis is associated with a high mortality rate. Aggressive endovascular management has led to survival rates of 35–50%. We report the largest series of endovascular reconstruction of occluded dominant vertebral arteries prior to basilar thrombectomy. Materials and methods: A prospective database since August 2010 of all neuroendovascular interventions was mined for patients undergoing basilar artery thrombolysis from which a group with vertebral artery reconstruction was selected. Patient charts were retrospectively reviewed for relevant clinical, technical, and outcome data. Results: From August 2010 to September 2012, six patients were identified who underwent vertebral reconstruction prior to basilar thrombectomy. Patients ranged in age from 42 to 57 years (mean 51 years). Mean time from symptoms until recanalization was approximately 6 h. Angiographic Thrombolysis in Cerebral Infarction IIB reconstitution of the basilar trunk was achieved in all cases. There were no technical complications. Two patients had care withdrawn secondary to massive completed brainstem infarction and poor neurological status post intervention. Three patients are now independent at 12, 14, and 31 months, respectively. One patient, after a follow-up of only 8 months, has achieved a modified Rankin Scale score of 3. Conclusions: Complete vertebral occlusion below a basilar thrombus can be recanalized prior to thrombectomy. In this case series, 100% of the acutely occluded vertebral arteries could be opened using either anterograde or retrograde access. However, basilar thrombosis continues to be a devastating illness, with one-third of the patients in this series dying of progressive infarction despite angiographic patency of the large conduit vessels with technical complications.